2009
DOI: 10.1016/j.abb.2009.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A study of human furin specificity using synthetic peptides derived from natural substrates, and effects of potassium ions

Abstract: We explored furin substrate requirements in addition to the motif R-X-K/R-R using synthetic fluorescent resonance energy transfer (FRET) decapeptides. These decapeptides were derived from furin cleavage sites in viral coat glycoproteins and human and bacterial protein precursors. The hydrolysis by furin of most substrate was activated by K+ ion, whereas kosmotropic anions of the Hofmeister series were inhibitors. The analysis of furin hydrolytic activity showed that its efficiency is highly dependent on the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 49 publications
2
60
0
1
Order By: Relevance
“…Cleavage efficiency at the furin and 2A recognition sites are both affected by the expressed proteins and the amino acids immediately surrounding their respective recognition sites. 33,35,43,44 P2A was reported to have the highest cleavage efficiency compared to the other 3 2A peptide in a previous study. 32 The low cleavage efficiency of P2A observed in this work could be due to the nature of HC and LC polypeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage efficiency at the furin and 2A recognition sites are both affected by the expressed proteins and the amino acids immediately surrounding their respective recognition sites. 33,35,43,44 P2A was reported to have the highest cleavage efficiency compared to the other 3 2A peptide in a previous study. 32 The low cleavage efficiency of P2A observed in this work could be due to the nature of HC and LC polypeptides.…”
Section: Discussionmentioning
confidence: 99%
“…3,6.17] with scores above zero indicating constraint (colored in white for scores < 0 and in shades of orchid for scores > 0). (Table S14) 58 We also undertook fine mapping 28 of 186 anthropometric trait loci established in the literature which also reached p % 5 3 10 À8 in the discovery stage (Table S4). We find that 14 credible sets 95% likely to contain the causal variant are narrowed down to a single variant, and 6 are narrowed down to 2 causal variants (Table S23).…”
Section: Fine-mappingmentioning
confidence: 99%
“…1A). Several biochemical studies have shown that the serine protease furin efficiently cleaves proteins containing these recognition sequences (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…Furin is a cellular endoprotease and has been implicated in the proteolytic activation of large numbers of secreted proteins (29,30). Inclusion of furin-cleavable linkers in fusion constructs containing ribotoxin, caspase-3, or granzyme B has resulted in a significant improvement in specific toxicity compared with constructs containing stable linkers (42,43).…”
Section: Discussionmentioning
confidence: 99%